PREVENTIVE AND PROMOTIVE ASPECT OF MUSIC THERAPY IN MANAGEMENT OF JOB STRESS WITH SPECIAL REFERENCE TO NURSING PROFESSION (International Journal of Ayurveda and Pharma Research, 2020)
World Health Organization stated that growing stress at workplace is epidemic now. A certain amount of stress and anxiety is normal at work place, but persistent, excessive, and irrational anxiety due to job stress causes various physical and psychological impairment. Nursing profession is a caring profession but it is identified as one of the most stressful job profession which affects not only physical and mental health of the nurses but also interfere in their job efficiency. Indian classical music is based on ragas. Ragas have power to alleviates and cures various ailments by inducing electromagnetic change in the body. Various studies indicating that Ragas improve psychological function of the body and simultaneously relaxing body and mind by enhancing alpha waves of the brain. The present write up is an effort to discuss the opportunities of Music Therapy for its preventive and health promotive dimensions specially to enhance quality of life of professionals and to overcome them from anxiety and depression develop due to job stress.